Quarant’anni di “Sozialpsychiatrische Informationen”, 1970-2009. Una breve cronaca - Elgeti, Hermann (Il sogno della farfalla, 2013)
Basing itself on oral testimonies and documentation contained within the published volumes, the history of the magazine “Sozialpsychiatrische Informationen” (INFO) is recounted, dating from the year of its foundation, 1970. 76 monographic issues were published in the last 25 years; in the article they are put into thematic groups. Moreover “provisional balances” on the evolution of the magazine are included. The approach of INFO includes the continuous (self)critical reflection on (social) psychiatry, with particular attention to the basic assumptions of a humanistic and social nature which have influenced it. A look at the price, the number of subscribers and the design of the magazine completes the picture.